Compensation Strategies and it's impact on Faculty Motivation in Community Colleges of Nepal - Mainali, Hari Lal; Pokharel, Dhurba Raj (Community College Research Journal, 2025)
Compensation strategies are widely recognized as critical in enhancing employee motivation and organizational performance. In the context of Nepal, particularly within community colleges in Madhesh Pradesh, limited attention has been given to how teaching faculty perceive such strategies. Grounded in the expectancy theory of motivation, this study sought to examine faculty perceptions of existing compensation systems and their alignment with institutional and regulatory frameworks.The study employed a descriptive and exploratory quantitative research design. Data were collected through structured, self-administered questionnaires distributed to full-time faculty members. Out of the total distributed, 87 valid responses were obtained. The data were analyzed using statistical techniques, including cross-tabulations and regression analysis.Findings revealed that existing compensation strategies were largely inadequate in meeting faculty expectations. Faculty members reported dissatisfaction and negative attitudes toward compensation systems. A central concern highlighted was the inconsistency between institutional practices and the regulatory frameworks mandated by Tribhuvan University. This misalignment appeared to weaken faculty motivation and potentially undermine the quality of instruction and overall academic outcomes.The study underscores the importance of aligning institutional compensation strategies with university guidelines to create a supportive and motivating work environment. By enhancing adherence to standardized compensation policies, institutions can improve faculty satisfaction, strengthen organizational effectiveness, and enhance educational quality. These insights are valuable for policymakers, administrators, and stakeholders aiming to improve governance and performance in Nepal’s community college sector.